PENGARUH PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS IX SMP NEGERI 24 PADANG - Fatmawati, Aulia (Departemen Matematika, 2023)
The ability to solve mathematical problems is very necessary for student, because they are must can understand problems, plan mathematical problem solving strategies, solve mathematical problems, and write final answers. The problem solving ability of ninth grade at junior high school Negeri 24 Padang is still low, because the learning process is teacher-centered. The solution to overcome this problem is to use the discovery learning model. The aim of this research to find out and explain the mathematical problem solving abilities of students whose learning uses the Discovery Learning model. This quasi-experimental research uses Nonequivalent Posttest Only Control Group Design. Results data analysis using the t-test obtained a value of which shows that the mathematical problem solving abilities of students who study with the discovery learning model is superior to those study with the conventional learning model at ninth grade junior high school Negeri 24 Padang.Keywords– Discovery Learning, Mathematical Problem Solving Ability